2014
DOI: 10.1021/jp507729w
|View full text |Cite
|
Sign up to set email alerts
|

Substrate, Molecular Structure, and Solvent Effects in 2D Self-Assembly via Hydrogen and Halogen Bonding

Abstract: Recently, halogen···halogen interactions have been demonstrated to stabilize two-dimensional supramolecular assemblies at the liquid−solid interface. Here we study the effect of changing the halogen, and report on the 2D supramolecular structures obtained by the adsorption of 2,4,6-tris(4-bromophenyl)-1,3,5-triazine (TBPT) and 2,4,6-tris(4-iodophenyl)-1,3,5-triazine (TIPT) on both highly oriented pyrolytic graphite and the (111) facet of a gold single crystal. These molecular systems were investigated by combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 112 publications
1
66
1
Order By: Relevance
“…2b; consistent with previous work, we identify these interactions through Cl⋯H distances that are shorter than the sum of the Cl and H vdW radii, as shown in Table S1 in the ESI. 24,35 † The electron density associated with the chlorine atoms in the TCB molecule is anisotropically distributed, as shown in Fig. S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b; consistent with previous work, we identify these interactions through Cl⋯H distances that are shorter than the sum of the Cl and H vdW radii, as shown in Table S1 in the ESI. 24,35 † The electron density associated with the chlorine atoms in the TCB molecule is anisotropically distributed, as shown in Fig. S2.…”
Section: Resultsmentioning
confidence: 99%
“…22 Gas-phase density functional theory (DFT) calculations were carried out using Gaussian09. 23 In previous work, we compared the performance of a number of functionals and basis sets for calculations of self-assembled systems comprising X⋯H and X⋯X interactions, 24,25 and found that the combination of M06-…”
Section: Methodsmentioning
confidence: 99%
“…[23] The fact that the surface and the solvent matters, and quite significantly so, was illustrated by comparison of self-assembly of 2,4,6-tris(4-iodophenyl)-1,3,5-triazine (2, inset Figure 3a) and 2,4,6-tris(4-bromophenyl)-1,3,5-triazine (3, inset Figure 3c) on HOPG and on Au(111). [24] It was originally intended that by changing the type of halogen, molecule-substrate interactions can be modulated, and thus one would observe differences in packing of these two molecules. However, both molecules formed similar close-packed assemblies on HOPG, which are stabilized by a combination of halogen···halogen interactions and halogen···H hydrogen bonds.…”
Section: Halogen-halogen and Halogen-heteroatoms Interactions At The mentioning
confidence: 99%
“…(f) DFT calculated model for the two-component monolayer showing co-adsorption of heptanoic acid. Reproduced from ref [24]. with permission from the American Chemical Society.…”
mentioning
confidence: 99%
“…53 Gatti et al observed that solvent molecules can sometimes interact with molecules without an alkyl chain and form a 2D bicomponent structure on Au(111). 54 In this paper the concentration-dependent self-assembly of 1,3,5-tris(4-iodophenyl)benzene molecules at the 1-phenyloctane/graphite interface is investigated. These molecules do not have alkyl chains.…”
Section: ■ Introductionmentioning
confidence: 99%